2014
DOI: 10.1155/2014/314262
|View full text |Cite
|
Sign up to set email alerts
|

Case of Thyrotoxic Periodic Paralysis in a Caucasian Male and Review of Literature

Abstract: Objective. Thyrotoxic periodic paralysis (TPP), a known condition in Asian men, is becoming increasingly common in men from Western countries. Since suspicion for TPP as a differential in diagnosis is of utmost importance to avoid overcorrection of hypokalemia and other complications, we are reporting a case of TPP in a 25-year-old Caucasian male. Methods. The patient presented with intermittent lower extremity weakness after consumption of a large high-carbohydrate meal. Clinical examination revealed diffusel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…If thyrotoxicosis is confirmed, then measurement of thyroid antibodies including TRAb should be carried out, especially as Graves' disease is the most common cause of TPP [1]. Although predominantly encountered in young Asian males, we together with other authors [3,16] have shown that TPP can appear irrespective of age, sex, and race, and thus, one should stay alert when facing hypokalemic paralysis. [5,15].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…If thyrotoxicosis is confirmed, then measurement of thyroid antibodies including TRAb should be carried out, especially as Graves' disease is the most common cause of TPP [1]. Although predominantly encountered in young Asian males, we together with other authors [3,16] have shown that TPP can appear irrespective of age, sex, and race, and thus, one should stay alert when facing hypokalemic paralysis. [5,15].…”
Section: Discussionmentioning
confidence: 98%
“…The usually subtle presentation of thyrotoxicosis accompanying TPP challenges the diagnosis [14]. Increased and elevated BP are more sensitive indicators of TPP than other hyperthyroid signs (fever, moist skin, exophthalmos, and goiter) [3]. In the ED, one should think of TPP if in front of the following criteria: (1) clinical and/or biochemical signs of thyrotoxicosis: a tachycardic patient with systolic hypertension and abnormal ECG (AV block) and/or low TSH together with high FT4 and FT3, (2) hypokalemia with low urinary K + excretion and normal blood acid-base status (hypophosphatemia and mild hypomagnesemia can also be encountered), and (3) negative family history for periodic paralysis [1,5,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During this disease, findings include QT-U that is prolonged, a prolonged PR, and resting sinus tachycardia. Although nerve stimulation studies are not necessary for diagnosis, if performed during the paralytic episode, there is a decrease in both compound muscle action potential and the amplitude of the evoked muscle action potential [12].…”
Section: Discussionmentioning
confidence: 99%